The derivatives of the functions are listed below:
(a)
(b) ![f'(x) = \frac{1}{3}\cdot (x + 3)^{-\frac{2}{3} }\cdot (x+ 5)^{\frac{1}{3} } + \frac{1}{3} \cdot (x + 5)^{-\frac{2}{3} } \cdot (x + 3)^{\frac{1}{3} }](https://tex.z-dn.net/?f=f%27%28x%29%20%3D%20%5Cfrac%7B1%7D%7B3%7D%5Ccdot%20%28x%20%2B%203%29%5E%7B-%5Cfrac%7B2%7D%7B3%7D%20%7D%5Ccdot%20%28x%2B%205%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%20%7D%20%2B%20%5Cfrac%7B1%7D%7B3%7D%20%5Ccdot%20%28x%20%2B%205%29%5E%7B-%5Cfrac%7B2%7D%7B3%7D%20%7D%20%5Ccdot%20%28x%20%2B%203%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%20%7D)
(c) f'(x) = [(cos x + sin x) · (x² - 1) - (sin x - cos x) · (2 · x)] / (x² - 1)²
(d) f'(x) = (5ˣ · ㏑ 5) · ㏒₅ x + 5ˣ · [1 / (x · ㏑ 5)]
(e) f'(x) = 45 · (x⁻⁵ + √3)⁻⁸ · x⁻⁶
(f)
(g)
(h) f'(x) = cot x + cos (㏑ x) · (1 / x)
<h3>How to find the first derivative of a group of functions</h3>
In this question we must obtain the <em>first</em> derivatives of each expression by applying <em>differentiation</em> rules:
(a) ![f(x) = 2 \cdot x^{-\frac{7}{2} } - x^{2} + 4 \cdot x - \frac{x}{5} + \frac{5}{x} - \sqrt[11]{2022}](https://tex.z-dn.net/?f=f%28x%29%20%3D%202%20%5Ccdot%20x%5E%7B-%5Cfrac%7B7%7D%7B2%7D%20%7D%20-%20x%5E%7B2%7D%20%2B%204%20%5Ccdot%20x%20-%20%5Cfrac%7Bx%7D%7B5%7D%20%2B%20%5Cfrac%7B5%7D%7Bx%7D%20-%20%5Csqrt%5B11%5D%7B2022%7D)
Given
Definition of power
Derivative of constant and power functions / Derivative of an addition of functions / Result
(b) ![f(x) = \sqrt[3]{x + 3} \cdot \sqrt[3]{x + 5}](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Csqrt%5B3%5D%7Bx%20%2B%203%7D%20%5Ccdot%20%5Csqrt%5B3%5D%7Bx%20%2B%205%7D)
Given
Definition of power
Derivative of a product of functions / Derivative of power function / Rule of chain / Result
(c) f(x) = (sin x - cos x) / (x² - 1)
- f(x) = (sin x - cos x) / (x² - 1) Given
- f'(x) = [(cos x + sin x) · (x² - 1) - (sin x - cos x) · (2 · x)] / (x² - 1)² Derivative of cosine / Derivative of sine / Derivative of power function / Derivative of a constant / Derivative of a division of functions / Result
(d) f(x) = 5ˣ · ㏒₅ x
- f(x) = 5ˣ · ㏒₅ x Given
- f'(x) = (5ˣ · ㏑ 5) · ㏒₅ x + 5ˣ · [1 / (x · ㏑ 5)] Derivative of an exponential function / Derivative of a logarithmic function / Derivative of a product of functions / Result
(e) f(x) = (x⁻⁵ + √3)⁻⁹
- f(x) = (x⁻⁵ + √3)⁻⁹ Given
- f'(x) = - 9 · (x⁻⁵ + √3)⁻⁸ · (- 5) · x⁻⁶ Rule of chain / Derivative of sum of functions / Derivative of power function / Derivative of constant function
- f'(x) = 45 · (x⁻⁵ + √3)⁻⁸ · x⁻⁶ Associative and commutative properties / Definition of multiplication / Result
(f) ![f(x) = 7^{x\cdot \ln x} + (x \cdot \ln x)^{7}](https://tex.z-dn.net/?f=f%28x%29%20%3D%207%5E%7Bx%5Ccdot%20%5Cln%20x%7D%20%2B%20%28x%20%5Ccdot%20%5Cln%20x%29%5E%7B7%7D)
Given
Rule of chain / Derivative of sum of functions / Derivative of multiplication of functions / Derivative of logarithmic functions / Derivative of potential functions
Distributive property / Result
(g) ![f(x) = \arccos^{2} x - \arctan (\sqrt{x})](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Carccos%5E%7B2%7D%20x%20-%20%5Carctan%20%28%5Csqrt%7Bx%7D%29)
Given
Derivative of the subtraction of functions / Derivative of arccosine / Derivative of arctangent / Rule of chain / Derivative of power functions / Result
(h) f(x) = ㏑ (sin x) + sin (㏑ x)
- f(x) = ㏑ (sin x) + sin (㏑ x) Given
- f'(x) = (1 / sin x) · cos x + cos (㏑ x) · (1 / x) Rule of chain / Derivative of sine / Derivative of natural logarithm /Derivative of addition of functions
- f'(x) = cot x + cos (㏑ x) · (1 / x) cot x = cos x / sin x / Result
To learn more on derivatives: brainly.com/question/23847661
#SPJ1